Penggunaan Alat Komunikasi Grup Whatsapp Dalam Pembelajaran Seni Tari Di Kelas VIII 1 SMP Negeri 2 Bukittinggi - Reski Suci; Yuliasma Yuliasma (SENDRATASIK UNP, 2020)
This study aims to determine the use of whatsapp group as a communication tool in dance learning in class VIII.1 at SMP Negeri 2 Bukittinggi. This is a qualitative research with a qualitative descriptive method. The instrument used in this study was a knowledge (cognitive) test. The data used were primary and secondary data. The data were collected through observation, interviews, learning outcomes tests, documentation, and literature study. The data analysis was conducted by reducing the data, presenting the data, and making conclusions. The results show that the implementation of learning method using Whatsapp group in class VIII.1 at SMP N 2 Bukittinggi is quite effective. Judging from the planning, the teacher's learning design remains the same. However, the learning steps conducted is different due tothe fact that it is carried out through WhatsApp group application. Meanwhile, the material is in the form of power points sent into the WhatsApp group chat as the learning media. Judging from the process of learning implementation, the material taught by the teacher is only the basic competence of knowledge, while the basic competence of skills is not. Thus, learning happens just for Basic Competence 3 while Basic Competence 4 is not implemented. In the learning process, the teacher always invites students to interact, but only a few students respond.The students responding are almost always the same while the other students only read the group because they are not familiar with learning using WhatsApp. Related to assignments given, the students always do well even though the materials provided by the teacher are incomplete. Every assignment can be done because students can search for answers by browsing the internet. Thus, students can add information that has not been given by the teacher.